Pengembangan Integrasi Budidaya Ikan Lele Dan Tanaman Herbal Di UPR Doa Mandeh - Fitrani, Mirna; Mukti, Retno Cahya; Fatmawati, Fatmawati; Yonarta, Danang (STMIK Royal, 2024)
The catfish cultivation business carried out by UPR Doa Mandeh since 2015 still requires support in the form of assistance and training for its development. Meanwhile, the availability of fish seeds in South Sumatra is still very dependent on other regions, such as Lampung, Jambi and West Java. The lack of use of appropriate catfish cultivation technology and the use of commercial feed has an impact on the low production of fish seeds produced. Apart from that, there has been no effort to treat waste water which has the potential to have a negative impact on the surrounding environment. For this reason, community service (PPM) is carried out, which applies lecture materials, research and publications that have been carried out by the proposing team in the form of application of biofloc technology, making liquid fertilizer and cultivating herbal plants. The aim and benefits of carrying out this activity are to develop the catfish cultivation business, increase seed production, utilize waste water from catfish rearing media into liquid fertilizer products that can be used to develop herbal plant cultivation which will ultimately increase the income of cultivators at UPR Doa Mandeh. The activity model is in the form of empowerment, development and assistance which is implemented using counseling, training and technical/production assistance methods. The results of this activity are high survival and growth rates for catfish, water quality is in the optimal range, and the richness of nutrients in wastewater from the biofloc system can be used as liquid fertilizer for herbal plants. Keywords: biofloc; catfish; herbal plants; liquid fertilizer